2023
DOI: 10.1021/acs.jctc.2c00919
|View full text |Cite
|
Sign up to set email alerts
|

Redox Potentials with COSMO-RS: Systematic Benchmarking with Different Databases

Abstract: Recent techniques of computational electrochemistry can yield redox potentials with accuracy as good as 0.1 V. Yet, many such methods are not universal, easy to use, or computationally efficient. Herein, we provide a systematic benchmarking of a relatively cheap and straightforward computational approach for fairly accurate computations of redox potentials. It is based on a combination of the conductor-like screening model for real solvents (COSMO-RS) and the density functional theory (DFT). The benchmarking i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…Finally, in addition/dissociation of species (H 2 O or CHF 2 COO – ), we employed the 1.9 Δ n kcal·mol –1 “standard state” conversion, where Δ n is the molar change in the process. It must be re-emphasized that all of the above computational approaches have been tested and verified against experimental data in our previous studies. ,, …”
Section: Methodsmentioning
confidence: 99%
“…Finally, in addition/dissociation of species (H 2 O or CHF 2 COO – ), we employed the 1.9 Δ n kcal·mol –1 “standard state” conversion, where Δ n is the molar change in the process. It must be re-emphasized that all of the above computational approaches have been tested and verified against experimental data in our previous studies. ,, …”
Section: Methodsmentioning
confidence: 99%
“…This process is straightforward and has been explored by others for different sets of molecules . It has been concluded that highly sophisticated quantum chemistry methods offer no advantages as the accuracy of the potentials is limited to around 0.3 V (MAE) when implicit solvation approximation is employed . We expect this performance from the best performing functionals here as well, so we only provide a brief analysis of functional performance and will focus more on the solvation effects present in our molecule set.…”
Section: Resultsmentioning
confidence: 99%
“…As we have seen, the best performing functionals indeed approach the accuracy limit set by the implicit solvent model . Therefore, to further improve the results, we need to understand better the solvation effects present in our benchmark set of PCs.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the cluster-continuum approach, we also employed the conductor-like screening model for real solvents (COSMO-RS) to evaluate the hydration free energies of the Cl – , BF 4 – , and BH 4 – anions. This is a pragmatic solvent model capable of providing accurate results in a wide range of cases . First, we calculated the gas-phase and aqueous-phase properties of all three ions.…”
Section: Methodsmentioning
confidence: 99%